Development, manufacturing and characterization of a new composite prepared from Cyperus corymbosus rotth and poly(Vinyl chloride) - Bootkul D. (2017)
© 2017 Trans Tech Publications, Switzerland. This research was focused on the study of the synthesis process, and the physical and mechanical properties, of the composite material prepared from Poly(vinyl chloride) (PVC) and natural fiber extracted from reed, scientific namely Cyperus corymbosus Rotth, leading to the development of a new type of low cost material for the furniture function. Reed is chosen to be a source of natural fiber due to its ease of finding and ease of growth along water reservoir which can provide a cheap material for composite production. In the study, the samples were divided into four groups based on the addition of reed powder loading, ranged from a weight ratio of 0%, 20, 40 to 50%, respectively. The composite materials were pre-mixed, using white oil as coupling agent, by the single screw extruder, and the wood plastic was produced by compression molding method. The flat plate panels were tested by several standard techniques, including impact testing, bending testing and tensile testing. Morphology of the fracture surfaces and the dispersion of filler particles were observed by using scanning electron microscopy (SEM). The testing measurement revealed the decreasing of impact strength, tensile strength and flexural strength in all WPCs in comparison with pure PVC. This negative effect may be ascribed to the poor compatibility between the fibers and polymer matrix.